2016
DOI: 10.1371/journal.pone.0163264
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Comparing Multi-Gene Biomarker Chip and Serum Carcinoembryonic Antigen in the Postoperative Surveillance for Patients with Stage I-III Colorectal Cancer

Abstract: BackgroundCirculating biomarkers can predict clinical outcomes in colorectal cancer patients. The aim of the study was to evaluate the feasibility of our multigene biomarker chip for detecting circulating tumor cells for postoperative surveillance of stage I–III colorectal cancer patients.Materials and MethodsIn total, 298 stage I–III colorectal cancer patients were analyzed after curative resection between June 2010 and October 2014. During each follow-up, a postoperative surveillance strategy, including ESMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…According to the Ministry of Health and Welfare of Taiwan, since 2006, CRC has become the most common cancer and the third most common cause of cancer-related death. In 2015, the incidence of CRC was 44.3 per 100,000 population, with 24.2 deaths per 100,000 population and an average of 12.9 years of life lost in Taiwan ( http://mohw.gov.tw/CHT/DOS/Index.aspx ; accessed in December 2016) [1] . Various molecular markers and many clinical epidemiological factors, such as being overweight or obese, physical inactivity, certain types of diets, smoking, heavy alcohol use, a personal history of inflammatory bowel disease, colorectal polyps or CRC, and family history of adenomatous polyps or CRC, have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ministry of Health and Welfare of Taiwan, since 2006, CRC has become the most common cancer and the third most common cause of cancer-related death. In 2015, the incidence of CRC was 44.3 per 100,000 population, with 24.2 deaths per 100,000 population and an average of 12.9 years of life lost in Taiwan ( http://mohw.gov.tw/CHT/DOS/Index.aspx ; accessed in December 2016) [1] . Various molecular markers and many clinical epidemiological factors, such as being overweight or obese, physical inactivity, certain types of diets, smoking, heavy alcohol use, a personal history of inflammatory bowel disease, colorectal polyps or CRC, and family history of adenomatous polyps or CRC, have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…26,383,518CanPatrol CTC enrichment(ISH) assay5 mL38 patients, 27 controls/BloodI–IVWu, 2015 11067%25,909,322PSG2, ELAVL4, TK1, UBE2C, PDE6D, PSAT1, CHRNB1, BMI1, CAP2, MMP13, OLFM4, PTTG1, MYC, MET, MUC1, HMGB1, hTERT, BIRC5,Enzyme immunoassay test kitCEA3 mL298 patients/BloodI–IIIChang, 2016 138-27,701,415PI3Kα, Akt-2, Twist1 ALDH1antiCD45 specific antibodies (Dynabeads, Invitrogen)qRT-PCR and multiplex-PCR_8 mL78 patients, 20 controls/BloodI–IVNing, 2018 129…”
Section: Resultsmentioning
confidence: 99%
“…The authors also found that the interval at which positive CTCs were detected was 6 months (range 3 to 8 months) earlier than that at which elevated CEA was detected. Likewise, in another cohort, elevated serum CEA and positive CTC results were the only two risk factors for postoperative recurrence, with odds ratios of 4.13 and 66.67, respectively [65]. Positive CTCs had higher sensitivity (87.5%) and specificity (92%) in predicting postoperative recurrence than CEA (60.4% and 83.2%, respectively), implying that the presence of CTCs was more powerful for predicting CRC recurrence than elevated CEA.…”
Section: Presence Of Ctcs and Postoperative Crc Recurrencementioning
confidence: 87%